Women's experiences of health care utilization in cases of early pregnancy loss: A scoping review. Issue 4 (July 2021) - Freeman, Angela; Neiterman, Elena; Varathasundaram, Shya
Abstract: Background: Approximately 25% of pregnancies end in miscarriage, most occurring within the first trimester (<13 weeks). For many women early pregnancy loss has implications for short- and long- term mental health, and women's well-being following early pregnancy loss is impacted by their experiences within the healthcare setting. To improve quality of care, it is crucial to understand women's' experiences within the healthcare system in cases of early pregnancy loss. Questions: What does the research literature tell us about the experiences of early pregnancy loss within healthcare settings? Are these experiences positive or negative? 'How can care improve for those experiencing early pregnancy loss?' Methods: A scoping review of the research literature was undertaken. Three research databases were searched for relevant articles published in English since 2009, with key words related to 'Experience', 'Healthcare' and 'Early Pregnancy Loss'. A thematic analysis was undertaken to identify and summarize key findings emerging from the research literature. Findings: Twenty-seven (27) articles met our inclusion criteria. Three main themes were identified: (1) issues related to communication, (2) challenges within care environments, and (3) inadequacies in aftercare. Discussion: The literature suggests that women's experiences related to healthcare for early pregnancy loss are largely negative, particularly within emergency departments. Recommendations to improve women's experiences should extend beyond attempts to improve existing care structures, to include emerging environments and providers. Conclusion: Women's experiences identified within the literature provide further insights on what women are seeking from their care, and how care models can be improved.